Florida Dampwood Termites, Neotermes castaneus (Burmeister), Neotermes jouteli (Banks), and Neotermes luykxi Nickle and Collins (Insecta: Isoptera: Kalotermitidae) - Rudolf H. Scheffrahn; Nan-Yao Su (EDIS)
This document is EENY-122 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2000.